Low-pressure chromatographic separation of p-hydroxybenzoates using sequential injection with lab-on-valve system and miniature monolithic column - Supaporn Kradtap Hartwell (2018)
The use of a small guard column (5-mm length) as a miniature analytical column in low-pressure liquid chromatography based on a sequential injection with lab-on-valve system was demonstrated. A strong initial mobile phase was used to rapidly deliver the sample zone to the column prior to simultaneous separation of analytes with weaker mobile phase. Separation of methyl-, ethyl-, propyl-, and butyl-4-hydroxybenzoates (MP, EP, PP, and BP) was achieved within about 120 s with sufficient peak resolution (all higher than 1.3) using 2,500 μL of mobile phase (composed of 1,087 μL of MeOH) per run. Detection limits were found to be 6.5, 8.0, 0.5, and 0.6 μmol L-1for MP, EP, PP, and BP, respectively. The system was tested with common commercially available skin lotions and wet wipe products. The analysis results were in good agreement with those obtained from the high-performance liquid chromatography with a 10-cm-length packed column. © 2014 Springer-Verlag.